Experimental investigation of cold-formed steel shear walls with self-piercing riveted connections. (October 2018) - Xie, Zhiqiang; Yan, Weiming; Yu, Cheng; Mu, Tingting; Song, Linlin
Abstract: With the purpose of introducing a new connection to cold-formed steel structure, this paper presents an experimental investigation of cold-formed steel (CFS) shear walls with self-piercing riveted (SPR) connections under monotonic and reversed cyclic loading. The effects of loading type (Monotonic and Cyclic), rivet spacing at the steel sheet edges, rivet number at CFS framing joints, axial compression ratio, and the steel sheathing types (steel sheet sheathing and corrugated steel sheathing) on mechanical behavior and failure modes of CFS shear walls were investigated. The shear strength, initial stiffness, and ductility of CFS shear walls with SPR connections were evaluated by comparing to the results of CFS shear walls with self-drilling screw connections under the same condition. Lateral loading, safety factor, and resistance factor under the wind and seismic loads were determined in accordance with test results of CFS shear wall with SPR connections. The research indicated that the rivet spacing at the sheet edges was a key factor affecting failure modes and mechanical properties of CFS shear walls. The relationship of shear strength and ultimate deformation decreased linearly with the increase of the rivet spacing. Compared to CFS shear walls with self-drilling screw, CFS shear walls with SPR have significantly improved shear strength and stiffness. Safety factor and resistance factor recommended by AISI Seismic Design Standard are conservative for the wind and seismic design of CFS shear wall using SPR connections. Highlights: Pilot research on self-piercing rivet connections in cold-formed steel shear walls. Monotonic and cyclic full-scale experiments on shear walls. Lateral and vertical combined loading in test setup. Recommended design provisions for cold-formed steel shear walls using self-piercing revit.